Motion planning and tracking trajectory of an autonomous emergency braking pedestrian (AEB-P) system based on different brake pad friction coefficients on dry road surface - Abdullah, Z.; Peeie, M. H.; Zakaria, M. A.; Ishak, M. I.; Shahrom, M. A.; Kujunni, B. (Penerbit Universiti Malaysia Pahang, 2022)
Accidents between vehicles and pedestrians usually occur when a pedestrian is crossing the road. An Autonomous Emergency Braking Pedestrian (AEB-P) is introduced to prevent collisions between vehicles and pedestrians. However, the performance of an AEB-P will be reduced when the brake pad is worn out on a dry road. In this study, the motion planning, namely Vehicle Conditional Artificial Potential Field (VC-APF), including a warning signal and emergency brake phase that generate the vehicle’s deceleration, is proposed to analyze the effect of brake pad on the AEB-P performance. Then, the vehicle’s deceleration is tracked by the tracking trajectory, where the PI controller is adapted to provide the optimum braking force. The function of PI control is to ensure the vehicle’s deceleration is approaching the desired deceleration. The performance of the proposed method has been simulated on the dry road surface with different brake pad coefficients; 0.4, 0.35, and 0.24. The simulation results show that the vehicle manages to stop colliding with a pedestrian on the dry road surface at the minimum safety distance range of 2.7-2.9 meters.